Renal volume and cardiovascular risk assessment in normotensive autosomal dominant polycystic kidney disease patients. Issue 49 (December 2016) - Sans, Laia; Pascual, Julio; Radosevic, Aleksandar; Quintian, Claudia; Ble, Mireia; Molina, Lluís; Mojal, Sergi; Ballarin, José A.; Torra, Roser; Fernández-Llama, Patricia
Abstract : Abstract: Cardiovascular disease, closely related to an early appearance of hypertension, is the most common mortality cause among autosomal dominant polycystic kidney disease patients (ADPKD). The development of hypertension is related to an increase in renal volume. Whether the increasing in the renal volume before the onset of hypertension leads to a major cardiovascular risk in ADPKD patients remains unknown. Observational and cross-sectional study of 62 normotensive ADPKD patients with normal renal function and a group of 28 healthy controls. Renal volume, blood pressure, and renal (urinary albumin excretion), blood vessels (carotid intima media thickness and carotid-femoral pulse wave velocity), and cardiac (left ventricular mass index and diastolic dysfunction parameters) asymptomatic organ damage were determined and were considered as continuous variables. Correlations between renal volume and the other parameters were studied in the ADPKD population, and results were compared with the control group. Blood pressure values and asymptomatic organ damage were used to assess the cardiovascular risk according to renal volume tertiles. Even though in the normotensive range, ADPKD patients show higher blood pressure and major asymptomatic organ damage than healthy controls. Asymptomatic organ damage is not only related to blood pressure level but also to renal volume. Multivariate regression analysis shows that microalbuminuria is only associated with height adjusted renal volume (htTKV). An htTKV above 480 mL/m represents a 10 times higher prevalence of microalbuminuria (4.8% vs 50%, P  < 0.001). Normotensive ADPKD patients from the 2nd tertile renal volume group (htTKV > 336 mL/m) show higher urinary albumin excretion, but the 3rd tertile htTKV (htTKV > 469 mL/m) group shows the worst cardiovascular risk profile. Normotensive ADPKD patients show in the early stages of the disease with slight increase in renal volume, higher cardiovascular risk than healthy controls. An htTKV above 468 mL/m is associated with the greatest increase in cardiovascular risk of normotensive ADPKD patients with normal renal function. Early strategies to slow the progression of the cardiovascular risk of these patients might be beneficial in their long-term cardiovascular survival.